Pengaruh Pendekatan Science, Environment, Technology, and Society (SETS) Berbantuan PhET Simulations Terhadap Keterampilan Proses Sains Siswa - Lufinda Amalia; Fitri Nuraeni; Wina Mustikaati (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
This study aims to determine and analyze the influence and improvement of the Science, Environment, Technology, and Society (SETS) approach, supported by PhET Simulations, on students' science process skills. The background of this study is based on students' low science process skills, which are still unable to classify, predict, and interpret data because learning is not oriented towards a scientific approach. A quasi-experimental method was used, with a non-equivalent control group design. The samples of this study were fourth-grade students of SDN 3 Nagrikaler, divided into two groups: an experimental class and a control class, using a purposive sampling technique. Test results came from the collection of pre-test and post-test data on science process skills. Non-test data came from observation and documentation. The test results showed an effect of 68.9% and an increase of 0.6637, which is in the moderate category. Therefore, learning with the Science, Environment, Technology, and Society (SETS) approach, supported by PhET Simulations are influential and capable of enhancing students' science process skills in science learning.